THE DESCRIPTION OF THE FORMATION ALGORITHM OF THE MANAGEMENT MECHANISM OF SOCIO AND LABOR RELATIONS OF THE UKRAINIAN AVIATION TRANSPORT ENTERPRISES - Yarovyi, I. M. (Science and Transport Progress, 2008)
Social-labour relations at the enterprises of aviation transport from positions of their existence in the open economic system are investigated. The component elements of management mechanism of social-labour relations at the enterprises of civil aviation ofUkraineare considered. The set of parameters of algorithm of forming the management mechanism of social-labour relations is characterized.